Opportunity cost of thirst: Behavioral insights into water bottle use at airports - Karabatić, Mirela; Lovrić, Sandra; Kacian, Irina (Crisis Management Days, 2025)
There is no official data on the availability of free drinking water from the tap at airports. The aim of the study is to examine whether passengers are informed about the availability of free drinking water at the airport and whether they are willing to take water in a reusable bottle. The question arises as to what is the opportunity cost of not having an empty bottle ready when they are thirsty. The study examined whether there is a difference in the share of passengers who buy disposable water bottles at an airport that has access to drinking water from a fountain compared to an airport that does not have a drinking water fountain. How to influence consumer behavior and reduce water consumption from single-use plastic bottles?